Paramagnetic, near-infrared fluorescent Mn-doped PbS colloidal nanocrystals - Knott, Andrew N. (2013)
This dissertation describes the effect that the controlled incorporation of manganese (Mn) has on the optical and magnetic properties of colloidal PbS nanoparticles.]